Limbah Nenas Penerapan Limbah Nenas Fermentasi Untuk Pengembangan Ayam Kampung Di Desa Tangkit Baru Kabupaten Muaro Jambi - Noferdiman, Noferdiman; Suryono, Suryono; Jahidin, Jaya Putra (Fakultas Sains dan Teknologi, Universitas Jambi, 2024)
The objectives of this community service (PPM) are as follows: (1) the application of pineapple waste fermentation technology with Trichoderma viride fungi for kampung chicken feed, (2) improving the knowledge and skills of poultry farmers in formulating cost-effective rations, (3) enhancing the knowledge and skills of poultry farmers in more efficient management and better production. The implementation method of community service involves active interaction between the project team and the target groups, which include 40 community members and farmer groups. The key stages in the implementation of the PPM are as follows: (1) dissemination and training, (2) active participation of farmer group members with the establishment of a Technical Consultation Service (TCS) forum for consultation and dialogue between the project team and poultry farmers, (3) hands-on practice in kampung chicken production management and pineapple waste processing using fermentation technology, (4) monitoring and evaluation (Monev) of the community service program in the farmer groups of Tangkit Baru, Muaro Jambi. The results of the community service activities are as follows: (1) the dissemination and training sessions have successfully increased the knowledge and skills of the participants, with the dissemination being rated as good, (2) the application of fermented pineapple waste as kampung chicken feed has been well-received by the farmer groups and the community in Tangkit Baru, Muaro Jambi (3) the implementation of this PPM program has proven highly beneficial for poultry farmers and implementing institutions, as it serves as a platform for the transfer of knowledge and technology, particularly in the traditional and non-business-oriented kampung chicken farming practices, thus optimizing the outcomes of these practices and facilitating the development of kampung chicken farming businesses.